STUDY OF THE POSSIBILITY OF APPLICATION OF FRUIT AND BERRY PUREE AND SUBLIMITED BERRIES IN THE PRODUCTION OF CHOCOLATE TRUFFLE CANDIES - A. A. Polovtseva; A. V. Borisova (Современная наука и инновации, 2022)
This article presents a physic-chemical study of two types of mashed potatoes (mango and raspberry) that make up the truffle candies, as well as the possibility of using freeze-dried berries in handmade chocolate products. As a result of the study, it was found that adding fruit and berry puree to the recipe of truffle chocolates in an amount of 15% allows you to give the products a more refined taste, change the appearance. Both types of mashed potatoes complied with the requirements of regulatory documents. The use of freeze-dried raspberry berries as a sprinkling of truffle candies has reduced the bitterness of the products and added color, which can significantly expand the range of pastry products.